2003
DOI: 10.1590/s0021-75572003000100012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de soropositividade para toxoplasmose em gestantes

Abstract: The prevalence of seropositivity in the pregnant women studied is high and justifies the adoption of some primary and secondary preventive measures, until subsequent studies provide greater evidence concerning the rationalization of the diagnostic and therapeutic techniques regarding toxoplasmosis in pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
30

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 29 publications
4
9
0
30
Order By: Relevance
“…The high prevalence of acute toxoplasmosis during pregnancy found in this study was expected, since a high frequency of seropositivity (prevalence: 59.8%; 95% CI: 57.0-62.5%) in this population was reported in a previous study (Varella et al 2003).…”
Section: Discussionsupporting
confidence: 79%
“…The high prevalence of acute toxoplasmosis during pregnancy found in this study was expected, since a high frequency of seropositivity (prevalence: 59.8%; 95% CI: 57.0-62.5%) in this population was reported in a previous study (Varella et al 2003).…”
Section: Discussionsupporting
confidence: 79%
“…In Porto Alegre, three studies involving large populations of pregnant women showed prevalences of toxoplasmic infection between 54.3% and 61.1%, similar to the highest described internationally (Neves et al1994, Varella et al 2003, Reis 2006. The results indirectly show that pregnant women who have not yet been infected are highly vulnerable to primary infection.…”
supporting
confidence: 55%
“…No Brasil, estudos realizados com grávidas evidenciaram 67% de positividade em Londrina-PR 37 , e outras regiões de mesmo padrão social, também mostraram prevalência equivalente, como 59,8% em Porto Alegre-RS 44 , 51,6% em Uberlândia-MG 16 e 71,4% em São Bernardo do Campo-SP 16 .…”
Section: Discussionunclassified